IMPLEMENTASI METODE TRANSFORMASI FOURIER DAN SIMILARITY MEASUREMENT UNTUK PERBAIKAN CITRA UNDERWATER - Istanto Gultom; Nelly Astuti Hasibuan; Imam Saputra (STMIK Budi Darma, 2018)
Nowadays many people pursue photography, some make it a job and not many people pursue photography as a hobby and for fun. The object sought also varies, for example public places and even underwater objects. Underwater photography activities are usually called underwater photography which is done during scuba diving. There are several factors that influence image quality in underwater photography activities, one of which is caused by absorption and scattering of sunlight when it reaches the sea floor. This is an obstacle if you want to get high quality images. This is because some pixels are brighter than other shimmering pixels [1]. Image quality improvement is the right solution to fix the problem in the underwater imagery described above. The method used to improve image quality is Fourier Transformation and Similiarity Measurement. First improvements using Fourier transformation and after repairing, the distance between the two objects is similar, the image after repair and before repair.Keywords: Underwater Imagery, Fourier Transform, Similarity Measurement